ESTIMATED LEVELS OF PHENYTOIN IN BLOOD AND RESULTS THERAPY OF EPILEPSY PATIENTS - Satrio Wibowo Rahmatullah; Lukman Hakim; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Medicines with a narrow therapeutic range such as phenytoin require individual dose, monitoring, and strict assessment of the patient to maintain the safety of the patient. It is because small changes in systemic concentration can lead significant changes in the pharmacodynamic responses, such as subtherapeutic or toxic. This study aimed to determine the relationship between dose and phenytoin levels in the blood included clinical outcome of patients with epilepsy based on the duration of seizure-free at the Sleman Regional General Hospital, Yogyakarta. This study was a descriptive observational study. The sampling method was purposive sampling. The data was collected retrospectively on epilepsy patients with phenytoin treatment both inpatient and outpatient from January 2010 to December 2012, male or female who were routinely controlled for at least 6 consecutive months. Patients were grouped into monotherapy and combination therapy groups. Clinical outcome was observed through the duration of the seizure-free and devided into 2 categories i.e. < 6 months (poor outcome) and ≥ 6 months (a good outcome). The results showed that male (53.6%) have a greater percentage than female (46.4%). Estimated blood levels of phenytoin was in the average 5.30±4.03 mg/L. Based on the duration of seizure free, the results showed that the percentage of patients in monotherapy group had good and poor outcomes with 71.83% and 28.17% respectively, while only 50% patients in combination therapy group had good outcome.Keywords: phenytoin, epilepsy, nonlinear, clinical outcome